Dagli archivi di paesaggi a possibili musei virtuali - Sasso, Laura; Codato, Giovanna; Franco, Elena (Ri-Vista. Research for landscape architecture, 2015)
The title of the book coordinated by Laura Sasso “Archivi da mostrare, Paesaggi e architetture in rete per una rete di progetti” (“Archives, Landscapes and Architecture network for a network of projects”, NdT) wants to show the close relationships between the concept of archive considered as an open space, landscape as an archive of itself, the trinomial concept archive-museum-landscape. Graphics and tri-dimensional models have shown the possibility to plan a new archive and museum network in Turin’s metropolitan area, centered on the river Po and its affluents. Places and historic architectures were identified along this fluvial system apt to host polarities that can have the characteristics of a museum, an effective active preservation tool, truly original and innovative mediums to restore territories, rich with surprising potential. The study cases, analyzed and developed in their different aspects, illustrate the concept of the museum as a container of material that documents the museum that opens to the river, floods the river itself, and the landscape that is a museum of itself.